2010
DOI: 10.1186/1471-2334-10-34
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices (KAP) relating to avian influenza in urban and rural areas of China

Abstract: BackgroundStudies have revealed that visiting poultry markets and direct contact with sick or dead poultry are significant risk factors for H5N1 infection, the practices of which could possibly be influenced by people's knowledge, attitudes and practices (KAPs) associated with avian influenza (AI). To determine the KAPs associated with AI among the Chinese general population, a cross-sectional survey was conducted in China.MethodsWe used standardized, structured questionnaires distributed in both an urban area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
3
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 13 publications
(29 reference statements)
12
46
3
2
Order By: Relevance
“…The interest manifested toward knowledge by the respondents is a promising factor for early improvement of practices of animal husbandry and milk processing; this general interest acts as a factor for reducing exposure, not only to Brucella spp, but also to other zoonotic pathogens. The current study found that the level of education was an important predictor and was positively associated with the adoption of preventive practices: this correlation was observed in many KAPs surveys (Xiang et al, 2010;Holt et al, 2011;Khan et al, 2013;Lindahl et al, 2015). This study can help to develop appropriate policies of preventive measures by improving the knowledge and practice of farmers in sanitation, hygiene and waste management.…”
Section: Resultsmentioning
confidence: 91%
“…The interest manifested toward knowledge by the respondents is a promising factor for early improvement of practices of animal husbandry and milk processing; this general interest acts as a factor for reducing exposure, not only to Brucella spp, but also to other zoonotic pathogens. The current study found that the level of education was an important predictor and was positively associated with the adoption of preventive practices: this correlation was observed in many KAPs surveys (Xiang et al, 2010;Holt et al, 2011;Khan et al, 2013;Lindahl et al, 2015). This study can help to develop appropriate policies of preventive measures by improving the knowledge and practice of farmers in sanitation, hygiene and waste management.…”
Section: Resultsmentioning
confidence: 91%
“…also TV, newspaper and internet were respectively noted as the most important sources of information. [16] A study done in Thailand can confirm all these results in which TV was introduced as the most efficient source of information. [19]…”
Section: Discussionmentioning
confidence: 91%
“…In their studies, the performance of the participants was appropriate about washing hands in order to prevent from avian influenza and a significant percentage of people -even in villages- washed their hands well. [16]…”
Section: Discussionmentioning
confidence: 99%
“…And around 2.3 million birds had been destroyed during this period (OIE, 2013b Bangladesh is now at Pandemic alert period i.e. in Phase 3.The persons who slaughter, farm, rear, transport, sell and who are closely related with poultry are considered as high risk areas (Xiang et al, 2010). The presence in the household of dead or sick poultry acts as a risk factor (Fielding et al, 2005).…”
Section: S K Sarker and Othersmentioning
confidence: 99%